2016
DOI: 10.1080/08998280.2016.11929436
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarettes in the Media

Abstract: Electronic cigarettes (e-cigarettes) are an increasingly popular source of nicotine and an increasingly popular topic in the media. Concerns about potential hazards associated with e-cigarette use and advertising, especially to adolescents, have led to studies on e-cigarettes in both traditional media (TV, mail, print, and outdoor advertising) and social media (websites, social networking sites, blogs, and e-mails). This review presents a narrative description of available studies related to e-cigarettes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
(33 reference statements)
2
15
0
1
Order By: Relevance
“…Our findings further refine the social media marketing presence of IQOS, which aligns with prior research that has documented and characterized emerging tobacco products across different social media platforms [15][16][17][18][19][20][23][24][25]33]. We found that promotional IQOS posts were largely driven by stakeholders along the IQOS business chain.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings further refine the social media marketing presence of IQOS, which aligns with prior research that has documented and characterized emerging tobacco products across different social media platforms [15][16][17][18][19][20][23][24][25]33]. We found that promotional IQOS posts were largely driven by stakeholders along the IQOS business chain.…”
Section: Discussionsupporting
confidence: 87%
“…A content analysis of 112 leading brands of e-cigarettes, hookah, cigars, cigarettes, and smokeless tobacco products on six platforms (i.e., Instagram, Facebook, Twitter, YouTube, Pinterest, and Tumblr) suggested that most e-cigarettes, hookah, and cigar brands had official pages on at least two platforms and brand pages rarely used age gating, did not display warning messages, generally posted product images alone and used hashtags unrelated to tobacco [13]. Similar evidence on extensive exposures to ANDS across different social media platforms was also found in a number of studies [14][15][16][17][18][19][20] and a significant amount of such exposures featured content related to youth [19].…”
Section: Introductionsupporting
confidence: 52%
“…En la actualidad, al menos un tercio de los usuarios de CE dijo no haber fumado tabaco antes o no tener tabaquismo activo para el momento de inicio de consumo de CE (6,36). Entre las posibles razones que se encuentran a este fenómeno están el mercadeo y las campañas que muestran a celebridades consumiendo este producto, las imágenes evocativas y la existencia de sabores atractivos (37,38,39,40). Algunos estudios han evidenciado una preferencia importante por los dispositivos con sabores tanto en la población adolescentes como en los adultos (41).…”
Section: Aumento En El Uso De Sistemas Electrónicos De Administraciónunclassified
“…Due to the relatively limited number of studies, the rates of adverse events (AEs) or beneficial health impacts of e-cigarettes are not well known. However, proponents of e-cigarettes place more emphasis on the positive aspects of their use, particularly in the public media [2]. E-cigarettes are frequently positioned as a smoking cessation tool or as a clean, easy-to-use, and less harmful device.…”
Section: Introductionmentioning
confidence: 99%